2020
DOI: 10.3390/jcm9082606
|View full text |Cite
|
Sign up to set email alerts
|

Low PCSK-9 levels Are Associated with Favorable Neurologic Function after Resuscitation from out of Hospital Cardiac Arrest

Abstract: Endotoxemia after cardiopulmonary resuscitation (CPR) is associated with unfavorable outcome. Proprotein convertase subtilisin/kexin type-9 (PCSK–9) regulates low-density lipoprotein receptors, which mediate the hepatic uptake of endotoxins. We hypothesized that PCSK–9 concentrations are associated with neurological outcome in patients after CPR. Successfully resuscitated out-of-hospital cardiac arrest patients were included prospectively (n = 79). PCSK–9 levels were measured on admission, 12 h and 24 h therea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…An extensive investigation of PCSK9 revealed its novel potential functions, including the regulation of neuronal development, apoptosis and differentiation, but the precise role of PCSK9 in brain physiology remained unclear ( Mannarino et al, 2018 ). Moreover, high circulating PCSK9 levels were associated with unfavorable neurological function after resuscitation from out-of-hospital cardiac arrest ( Merrelaar et al, 2020 ). The increase in PCSK9 levels was most likely caused by the inflammatory response and organ dysfunction after cardiopulmonary resuscitation (CPR).…”
Section: Methodsmentioning
confidence: 99%
“…An extensive investigation of PCSK9 revealed its novel potential functions, including the regulation of neuronal development, apoptosis and differentiation, but the precise role of PCSK9 in brain physiology remained unclear ( Mannarino et al, 2018 ). Moreover, high circulating PCSK9 levels were associated with unfavorable neurological function after resuscitation from out-of-hospital cardiac arrest ( Merrelaar et al, 2020 ). The increase in PCSK9 levels was most likely caused by the inflammatory response and organ dysfunction after cardiopulmonary resuscitation (CPR).…”
Section: Methodsmentioning
confidence: 99%
“…The washout period was deemed sufficient based on the following assumptions: i) a terminal elimination half-life of micellar curcumin of 4-6 h from earlier studies was estimated, [38,39] ii) the study hypothesized that like other NF𝜅B inhibitors, any anti-inflammatory effects of curcumin were concentration-dependent, and iii) the study previously showed that PCSK9 was quickly regulated, and concentrations could adapt within a few hours to clinical conditions. [66,67] On the morning of the first study day, participants arrived at the Department of Clinical Pharmacology following an overnight fast. After baseline blood sampling, participants received a single dose of 35 mg curcumin (in the form of capsules containing either 43 mg of micellar curcuminoids or native curcuminoids).…”
Section: Methodsmentioning
confidence: 99%
“…The washout period was deemed sufficient based on the following assumptions: i) a terminal elimination half‐life of micellar curcumin of 4–6 h from earlier studies was estimated, [ 38 , 39 ] ii) the study hypothesized that like other NFκB inhibitors, any anti‐inflammatory effects of curcumin were concentration‐dependent, and iii) the study previously showed that PCSK9 was quickly regulated, and concentrations could adapt within a few hours to clinical conditions. [ 66 , 67 ]…”
Section: Methodsmentioning
confidence: 99%